Conflicts in heritage protection - Frowe, Helen ca. 20./21. Jh; Matravers, Derek 1965- (2023)
The Inseparability Thesis holds that protecting heritage is inseparable from protecting people and therefore cannot conflict with protecting people. This chapter argues that we ought to reject this thesis. Conflicts between protecting heritage and protecting people are rife, both within and without war. Most obviously, these conflicts occur in cases of scarce resources. But they also occur when we distribute the risks of war. Protecting heritage can require combatants to impose risks on civilians and to incur risks to themselves. Judging the permissibility of imposing such risks and ordering combatants to incur them demands not only that we recognise conflicts between protecting heritage and protecting people but also that we develop a rubric for comparing the moral significance of harms to each. Implementing the provisions of the 1954 Hague Convention on the Protection of Cultural Property in Times of Armed Conflict also demands the use of such a rubric.
Keywords: Konvention zum Schutz von Kulturgut bei bewaffneten Konflikten -- 1954 Mai 14; Zivilschutz; Kulturgüterschutz; Kulturerbe; Krieg